The Asean-China free trade agreement(ACFTA) - Hadi, Zufri (KDI School, 2012)
Free trade has become an interweaving phenomenon of the market in the globalized political economy. Indonesia is taking part in the framework of ASEAN-China Free Trade Agreement (ACFTA). Controversies on the anticipated impacts of ACFTA’s implementation on the Indonesian economy are legion across various economic strata: among people, economic observers, entrepreneurs and bureaucrats. This study is aimed at exploring the ACFTA’s impact to the Indonesian economy by examining the potential impacts on domestic sectors. Included in the examination are the changing of the international trade transaction, the economic growth (GDP per capita) and the changing of market share of Indonesian export commodities before and after its implementation. The analysis uses the Gravity Model, Revealed Comparative Advantage (RCA) and Intra-Industry Trade (IIT) Index. Overall, the result shows a positive impact; however there will be a significant decrease of the group commodities of chemicals and related products, miscellaneous manufactured articles, and the other commodities and transactions which are not classified in the Standard International Trade Classification (SITC).
Thesis(Master) --KDI School:Master of Public Policy,2012
Keywords: ACFTA